A framework for complaints and suggestions management system (CSMS) and e-CSMS - Mohamad @ Asmara, Salwana (2007)
Complaint is occurred when the provided services or products are unsuccessfully fulfilled the customer’s requirements and needs. Understanding the customer’s need is very important for the organization in purpose to deliver the best quality of services and products. Complaint and suggestion also closely related to quality management while sometimes, it has not been taken seriously by some organization especially in the government sector. Therefore, this project is done to derive a solution regarding to this matter by formulating CSMS (Complaint and Suggestion Management System) framework and a prototype of complaint and suggestion management online system, e-CSMS. Four case studies are done to achieve the best result of this project objective. This project is emphasized on the governmental services sector in handling complaints and suggestions whereby it is different from the private sector which is more profit centric. Hopefully, the result of this project will give a beneficial contribution for complaint and suggestion management system in order to improve the quality of services in government sector.